AN EFFORTS OVERCOME CRIME CAUSED TEENAGE DELINQUENCY BASED JUSTICE AS FAIRNEST - Rahul Ardian Fikri; Muhammad Azhali Siregar; M. Fikri Akbar (Jurnal Scientia, 2023)
This study concludes that the policy of law enforcement officials in handling the problem of juvenile delinquency by prioritizing restorative justice has built joint participation between perpetrators, victims and the community in resolving a criminal event. The provision of ta'zi>r punishment in minor crimes against children - perpetrators of criminal acts - with forgiveness and the provision of minimum sentences contains many elements of justice. This concept is in line with the principles of restorative justice. If the offender can be rehabilitated by other, better measures then punishment should be avoided. The author uses a qualitative research method with a normative juridical approach that is descriptive analytical in its data presentation. The data collection method in this research uses literature study, interview, and observation in accordance with the types of data sources needed. Data sources are obtained through interviews and observations with relevant legal institutions that handle juvenile criminal cases such as the Police, Community Research Officers (Bapas) and Juvenile Judges.